Studying the Scattering Mechanisms on Highly Transparent Polyisocyanurate–Polyurethane Aerogels - Merillas , Beatriz; Leon, Judith Martin-de; Villafane, Fernando; Rodriguez-Perez, Miguel Angel (Fundamental Research and Application of Physical Science Vol. 6, 2023)
Polyurethane-based aerogels have been synthesized and their optical properties studied in detail. The strong and direct relationship between the structural features of the produced materials with the final light transmittance allowed to analyze the scattering mechanisms. Thus, through the modification of the initial polyurethane formulations tunable structures were obtained and, consequently, their final optical properties were tailored. In this way, for aerogels with networks formed by small particles and pores, the highest transmittances were reached (85% at 650 nm). However, these values were progressively reduced with the enlarging of the structural features owing to the light scattering that they produce. Then, the transition through Rayleigh scattering to Mie scattering was determined by measuring the light transmittance at a wide range of light wavelengths (UV-Vis). Additionally, the Beer-Lambert law was verified for all the aerogels under study through the effect of the sample thickness on the final transmittance. Therefore, the optical properties of polyurethane aerogels were studied in detail, obtaining aerogels with tunable transmittances which opens a wide range of applications in building and energy sectors such as glazing windows.